Race and educational leadership: The influence of research methods and critical theorising in understanding representation, roles and ethnic disparities. (July 2021) - Maylor, Uvanney; Roberts, Lorna; Linton, Kenisha; Arday, Jason
The special issue offers new knowledge about racialised educational experiences by shedding light on racialised leadership in school and higher education in diverse geographical and educational contexts in England, Canada, America and South Africa through a mix of research methods (phenomenological, longitudinal, documentary, semi-structured interviews), analytical (content and textual analysis) and theoretical approaches (critical race theory [CRT], critical ecological). This special issue prioritises the centring of educational leaders' lived experiences and their voices alongside the research methods used to illuminate the nuances associated with race and educational leadership in schools and higher education. The prism of race enables us to add new educational leadership insights to the field associated with ethnicity, gender, culturally constructed notions of leadership, intersectionality and/or geographical location. The findings highlight implications for researching race and educational leadership.